Spatio-temporal distribution of Aedes aegypti (Diptera: Culicidae) mitochondrial lineages in cities with distinct dengue incidence rates suggests complex population dynamics of the dengue vector in Colombia. - Jeiczon Jaimes-Dueñez; Sair Arboleda; Omar Triana-Chávez; Andrés Gómez-Palacio (Public Library of Science (PLoS), 2015)
BACKGROUND:Aedes aegypti is the primary vector of the four serotypes of dengue virus (DENV1-4), Chikungunya and yellow fever virus to humans. Previous population genetic studies have revealed a particular genetic structure among the vector populations in the Americas that suggests differences in the ability to transmit DENV. In Colombia, despite its high epidemiologic importance, the genetic population structure and the phylogeographic depiction of Ae. aegypti, as well as its relationship with the epidemiologic landscapes in cities with heterogeneous incidence levels, remains unknown. We conducted a spatiotemporal analysis with the aim of determining the genetic structure and phylogeography of Colombian populations of Ae. aegypti among cities with different eco-epidemiologic characteristics with regard to DENV. METHODS/FINDINGS:Mitochondrial cytochrome oxidase C subunit 1 (COI)--NADH dehydrogenase subunit 4 (ND4) genes were sequenced and analyzed from 341 adult mosquitoes collected during 2012 and 2013 in the Colombian cities of Bello, Riohacha and Villavicencio, which exhibit low, medium and high levels of incidence of DENV, respectively. The results demonstrated a low genetic differentiation over time and a high genetic structure between the cities due to changes in the frequency of two highly supported genetic groups. The phylogeographic analyses indicated that one group (associated with West African populations) was found in all the cities throughout the sampling while the second group (associated with East African populations) was found in all the samples from Bello and in only one sampling from Riohacha. Environmental factors such as the use of chemical insecticides showed a significant correlation with decreasing genetic diversity, indicating that environmental factors affect the population structure of Ae. aegypti across time and space in these cities. CONCLUSIONS:Our results suggest that two Ae. aegypti lineages are present in Colombia; one that is widespread and related to a West African conspecific, and a second that may have been recently introduced and is related to an East African conspecific. The first lineage can be found in cities showing a high incidence of dengue fever and the use of chemical insecticides, whereas the second is present in cities showing a low incidence of dengue fever where the use of chemical insecticides is not constant. This study helps to improve our knowledge of the population structure of Ae. aegypti involved in the diversity of dengue fever epidemiology in Colombia.